2022
DOI: 10.1108/jpbm-09-2020-3091
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived scarcity on strengthening the attitude–behavior relation for sustainable luxury products

Abstract: Purpose This study aims to examine whether, and how, perceived product scarcity strengthens the attitude–behavior relation in the case of sustainable luxury products. Design/methodology/approach Three online studies were conducted to examine the moderating role of perceived product scarcity on the attitude–willingness to pay (WTP) relationship in the case of sustainable luxury products. A preliminary study (n = 208) examined the existence of an attitude–WTP gap toward a sustainable luxury product (i.e. a bag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 86 publications
(217 reference statements)
5
16
0
Order By: Relevance
“…This implies that consumers assign a higher value to products that can address contemporary environmental concerns. This finding aligns with previous research, which found green products to positively affect customer attitudes and willingness to pay (Filieri et al, 2021;Park et al, 2022). However, we did not observe any significant moderating effects for product type II (technological vs. non-technological) or sector (manufacturing vs. service).…”
Section: Discussionsupporting
confidence: 91%
“…This implies that consumers assign a higher value to products that can address contemporary environmental concerns. This finding aligns with previous research, which found green products to positively affect customer attitudes and willingness to pay (Filieri et al, 2021;Park et al, 2022). However, we did not observe any significant moderating effects for product type II (technological vs. non-technological) or sector (manufacturing vs. service).…”
Section: Discussionsupporting
confidence: 91%
“…By establishing linkages between the cognitive variables, i.e., subjective norms, attitude, perceived behavioural control and behavioural intention as prescribed by TPB (Ajzen, 1991), the researchers are increasingly applying this model to describe the attitude–intention relationships concerning sustainable consumer behaviour. However, very little literature exists that is considered to explain the relationships of attitude, intention and behaviour concerning sustainable consumer behaviour (Jaiswal & Singh, 2018; Park et al, 2022). In addition, scholars in this field have stressed upon investigating other cognitive constructs including environmental and psychological variables such as environmental concerns & knowledge, environmental outcomes, consumer innovativeness, consumer effectiveness and eco‐label knowledge/awareness for improving the explanatory power of this theory and to better describe the interrelationships of various important factors (Jaiswal & Kant, 2018; Taneja & Ali, 2021; Yadav & Pathak, 2017; Yin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One strategy that makes luxury products more desirable is to signal their scarcity by informing consumers of their limited quantity (Park et al, 2022). In this context, bars could consider offering only smaller sizes of craft beers, such as 20 or 33 cL, which could possibly increase the luxury aspect of craft beer consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Craft beer brands share many characteristics with luxury brands, such as uniqueness, with these brands often benefiting from rising unit prices (Gómez‐Corona et al, 2017; Kapferer & Bastien, 2009). One strategy that makes luxury products more desirable is to signal their scarcity by informing consumers of their limited quantity (Park et al, 2022). In this context, bars could consider offering only smaller sizes of craft beers, such as 20 or 33 cL, which could possibly increase the luxury aspect of craft beer consumption.…”
Section: Discussionmentioning
confidence: 99%